Changes in the epidemiology and prognosis of Streptococcus pyogenes necrotizing fasciitis after COVID-19: Insights from a university hospital - Guzmán-Sánchez, Álvaro; de la Villa, Sofía; Hernández-Mateo, Jose María; García-Quirós, María Asunción; Benjumea, Antonio; Matas, Jose Antonio; Sánchez-Somolinos, Mar; Vaquero, Javier; Sanz-Ruiz, Pablo (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Following the COVID-19 pandemic, numerous countries have reported a significant increase in invasive Streptococcus pyogenes infections. Our aim was to analyze the epidemiology, clinical characteristics, morbidity, and prognosis of patients with S. pyogenes-associated necrotizing fasciitis in the post-COVID-19 era. Methods: This retrospective study was conducted at a university hospital and included all consecutive adult patients (≥18 years) diagnosed with S. pyogenes-associated necrotizing fasciitis between 2012 and 2023. Two study periods were compared: pre-COVID-19 (2012–2019) and post-COVID-19 (2020–2023). The primary objective was to determine incidence (admissions per 100,000 inhabitants). Secondary outcomes included in-hospital mortality, length of hospital stay and intensive care unit admissions between the periods. Results: A total of 34 cases were included: 17 in the pre-COVID-19 period and 17 in the post-COVID-19 period, with an incidence of 0.42/100,000 vs. 1.13/100,000 inhabitants-year, respectively (P<0.01). Compared to the pre-COVID-19 period, patients in the post-COVID-19 period had lower Charlson comorbidity index score (median 2 vs. 5, P=0.04), and required fewer fasciotomies (median 1 vs. 3, P=0.01). In-hospital mortality was 17.6% in both periods, while the length of hospital stay was shorter in the post-COVID-19 period (median 15 vs. 29 days, P=0.04). Conclusions: Our findings reveal an increased incidence of S. pyogenes-associated necrotizing fasciitis following the COVID-19 pandemic, predominantly affecting younger patients with lower comorbidity and showing a trend toward better clinical outcomes. Further studies are needed to better understand the underlying factors driving these changes.